Influence of Excipients on the Structural and Mechanical Properties of Semisolid Dosage Forms - Kukhtenko, Ðalina (Asian Journal of Pharmaceutics (AJP), 2017)
Context: In the scientific article presents data are presented on investigation of the influence of nonaqueous solvents such as propylene glycol, polyethylene oxide-400 (PEO-400) and glycerin on the structural, and mechanical properties of the emulsion and gel coagulation systems. The regularity of the structural viscosity changes of the systems studied from concentrations of propylene glycol, PEO-400, glycerol, and combinations thereof have been determined. Aim: The aim of the work is to study the effect of propylene glycol, PEO-400, and glycerol on the rheological (structural and mechanical) properties of soft dosage forms. Materials and Methods: The objects of research were concentrated (creamy) 1 kind emulsion systems and gel formulations. Three series of samples were prepared. All samples were subjected to rheological studies on rheoviscometer â€œRheolabQCâ€ of company Anton Paar (Austria). Results: It has been found that glycerol in an amount up to 5% increases the viscoplastic properties of emulsion systems, at its concentration above 5% there is a decrease in these properties. Propylene glycol and PEO-400 at a concentration of 5%, on the contrary, lower viscoelastic properties of emulsion systems, at their concentrations from 5% to 15% there is an increase in the structural viscosity of the concentrated emulsion and at a concentration of more than 15% the systems thin. At the introduction of propylene glycol and PEO-400 in the gel coagulation system in concentrations of up to 30%, viscoplastic properties increase slightly. Increasing the amount of these substances to 60% in a different degree affects the structural viscosity of the gel system, so propylene glycol in the concentration of 60% reduces structural viscosity from 34.9 to 19.4 Paâˆ™s at shear rate of 10.4 Pa, and introduction of 60% PEO-400 - 4.8 Paâˆ™s at the same shear rate. Combining these substances in the formulation leads to potentiating each otherâ€™s action. Conclusions: Introduction of propylene glycol, PEO-400 and glycerol to soft medicinal forms allows varying their viscoelastic properties. It should be outlined that the ability to modify the thixotropic properties of both the emulsion and gel systems are more pronounced in the PEO-400.